Teaching Materials of Local Wisdom-Based E-Book in Digital Learning: A Systematic Literature Review - Amilul Ulum, Uyung; Muhyidin, Asep; Jamaludin, Ujang (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
The growing demand for culturally responsive digital learning highlights the importance of developing local wisdom-based e-book teaching materials to enrich online education and strengthen students' cultural identity. Following PRISMA guidelines, this study presents a systematic literature review of local wisdom-based e-book teaching materials in digital learning. Articles included were published between 2017 and 2024, written in English, relevant to the topic, and indexed by at least SINTA. Literature searches were conducted through ScienceDirect, ERIC, Google Scholar, Springer, Scopus, and Web of Science databases. The findings show that strategies for developing these materials include integrating e-learning, gamification, augmented reality (AR), and virtual reality (VR); using project-based challenges involving cultural practitioners; and incorporating portfolios and local wisdom content. The impact of local wisdom-based e-books includes strengthening students’ character (love of the homeland, peace-loving attitudes, and social care), enhancing critical thinking, scientific reasoning, and conceptual understanding, and improving digital literacy, science literacy, creative writing, and communication skills. This study concludes that local wisdom-based e-book teaching materials have strong potential to enhance student engagement and foster cultural identity in digital learning environments.